2020
DOI: 10.2147/idr.s281097
|View full text |Cite
|
Sign up to set email alerts
|

<p>Surgical Site Infections and Prophylaxis Antibiotic Use in the Surgical Ward of Public Hospital in Western Ethiopia: A Hospital-Based Retrospective Cross-Sectional Study</p>

Abstract: Objective: Surgical site infection (SSI) is one of the leading causes of hospital-acquired infection among hospitalized patients. It causes significant health problems and results in an extended length of hospital stay, increased cost, and increased patient morbidity and mortality. To prevent the development of SSI, surgical antibiotic prophylaxis (SAP) administration before surgery is an evidence-based practice. Therefore, this study aimed to assess the prevalence of SSIs and surgical antibiotic prophylaxis p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 45 publications
2
22
1
Order By: Relevance
“…The most remarkable finding of the study is that monotherapy (64.9%) was chosen over combination therapy since most preventive antibiotics were administered empirically, with cephalosporins accounting for 56.8 percent of all antibiotic encounters. Ceftriaxone was the most usually administered third generation cephalosporin in most surgeries; however, cefotaxime or cefoperazone was apparently the most regularly prescribed third generation cephalosporin in a few studies [17,[27][28][29][30]. It has been reported that the most common therapeutic errors in general surgery were administration of second-or third-line antibiotics without indication and use of antibiotics when they were not required [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…The most remarkable finding of the study is that monotherapy (64.9%) was chosen over combination therapy since most preventive antibiotics were administered empirically, with cephalosporins accounting for 56.8 percent of all antibiotic encounters. Ceftriaxone was the most usually administered third generation cephalosporin in most surgeries; however, cefotaxime or cefoperazone was apparently the most regularly prescribed third generation cephalosporin in a few studies [17,[27][28][29][30]. It has been reported that the most common therapeutic errors in general surgery were administration of second-or third-line antibiotics without indication and use of antibiotics when they were not required [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Our finding that ceftriaxone alone was commonly used for preoperative antibiotic prophylaxis matches other reports from Ethiopia. 21,22 A 2019 report from a government hospital in southern Ethiopia found that ceftriaxone reasonably covers most pathogens implicated in SSIs from clean procedures based on local susceptibility patterns, though first-generation cephalosporins, such as cephazolin, are generally preferred for most procedures to reduce antimicrobial resistance. 8,23,24 Unfortunately, several studies from Ethiopia suggest first-generation cephalosporins are less widely available than ceftriaxone.…”
Section: Discussionmentioning
confidence: 99%
“…Chautrakarn et al and Kefale et al reported inappropriate use of antibiotics in the surgical ward; mainly due to the inappropriate selection of antibiotics [58,59]. Tiri et al reported that out of 2059 elective surgical procedures, the dose was appropriate with a rate of 69.7% and that the choice of antibiotic was appropriate with a rate of 78.4% [40].…”
Section: Inappropriate Selection and Dosingmentioning
confidence: 99%